If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x^-6*e^(6*x)
e^6*x^-6*x
65.5/400
3*cos(2*c)
(2*x^4-x)/(x^3)
| 2(3x)+1=2+21 | | 16x^2+160t-300=0 | | ln(2x-6)=ln(x-3) | | -10=5(y+4)-2y | | 3x+7xy-8x+5y= | | 18.3+Q=-5 | | 2-2i=0 | | 3.14*x^2/4 | | 3.4x-3=32.8 | | .03x+100=.07x | | 4x=19-(-1) | | 13=4(u-2)-7u | | Y=(4-4x)/2 | | 5+12i=1 | | 5x+7.2=32.8 | | -24x-188=-28x+100 | | 6x-8xy=-11 | | -39=5(v+5)+3v | | (4-4x)/2 | | 2-2i=1 | | 6/x=4 | | 3x^2+4y^2+3xy=24 | | 12(p-36)=3888 | | -15=4(w-2)+3w | | -4-2y=0 | | 3x^2=12-9 | | 100+.03x=.07x | | 4x+60-2x=180 | | 8x^2-24x+20=0 | | 6(-6+x)=-36 | | 2(0.333333333x+4)-6=-0.333333333(3x-21) | | x=1/4x^2 |